Pola Penerapan Apresiasi Seni 2D Melalui Playmat Audio Visual Interaktif Berbasis Gamifikasi untuk Guru PPG Seni Budaya Dalam Jabatan - Abdul Rahman Prasetyo; Putra Hilmi Prayitno; Fikri Aulia; Eka Putri Surya; Nila Rahmawati; Adinda Marcelliantika; Alby Aruna (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Exploration of the application of 2D art appreciation patterns through the use of gamification-based interactive audio visual playmats designed specifically for in-service PPG Arts and Culture teachers. A qualitative approach with a case study design was used as a research method, with data collected through in-depth interviews, participant observation, and analysis of related documents. The results show that the use of gamification-based interactive playmats can increase teacher interest and involvement in appreciating 2D works of art. Apart from that, this playmat has also proven effective in developing teachers' critical analysis skills and aesthetic understanding. These findings provide significant implications for the development of more innovative and interactive arts and culture teaching methods, supporting the improvement of the quality of arts education in Indonesia. Thus, this method not only stimulates teacher interest and involvement, but also enriches their understanding of works of art, so that it can be applied in the learning process in various educational contexts.